FOREIGN DIRECT INVESTMENT AND ONE DIGIT STANDARD INTERNATIONAL TRADE CLASSICIFICATION - Murman Budijanto; Bagus Rachman (Economic Journal of Emerging Markets, 2010)
The relationship between trade and Foreign Direct Investment (FDI) has been indicated as one of prominent development paths toward economic development. However, this relation is not straightforward due to the complex multinational companies’ investment motivation. This paper develops an exploratory research on the FDI-trade relation in one digit Standard International Trade Classification (SITC) for Indonesia with Japan and the United States of America during 1991-2003, using a Granger causality test. The result indicates strong FDI-trade relationship in natural resources and mining industry, showing that resources endowment is an advantage for Indonesia. It also finds that resource-seeking FDI has predominantly happened during that period.Keywords: Foreign direct investment, trade, one-digit SITC, granger causalityJEL classification numbers: F12, F14